Characteristics, multi-functionality, and water quality of reservoirs in North-East Ghana: Field Survey Report - Amponsah, Mary (2023)
The report present the results from the field study executed as part of the activities of the WP3 of the Aquatic Foods Initiative. It describes the characteristics, water uses and users, and water quality of eight reservoirs visited in North-East Ghana. The results will support the final selection of the pilot sites for fish-cage farming in selected reservoirs.